2018
DOI: 10.1002/dc.24039
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration of alveolar soft part sarcoma: Histologic correlation and aberrant CD68 expression

Abstract: Alveolar soft part sarcoma is a rare highly malignant neoplasm of the soft tissue and usually occurs in the lower extremities of children and young adults. We report two cases of alveolar soft part sarcoma: a 24-year-old Latino man with a 10-cm neck mass and a 56-year-old Latino woman with a recurring thigh mass. Fine-needle aspiration and a core biopsy were performed on both, which was followed by tumor resection on the man. The smears displayed numerous loosely cohesive or single large cells with abundant gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Only three cases of primary pulmonary ASPS have been reported till date [30]. This is the first case reporting its cytomorphology, while the existing literature on the cytomorphology of ASPS is already extremely limited [31,32]. Cells with large, vesicular nuclei, prominent eosinophilic macronucleoli, and abundant cytoplasm seen in ASPS (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Only three cases of primary pulmonary ASPS have been reported till date [30]. This is the first case reporting its cytomorphology, while the existing literature on the cytomorphology of ASPS is already extremely limited [31,32]. Cells with large, vesicular nuclei, prominent eosinophilic macronucleoli, and abundant cytoplasm seen in ASPS (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Paragangliomas also display TFE3 positivity, in addition to markers of neuroendocrine differentiation 4 . While Nambirajan et al 11 reported an aberrant CD10 immunoexpression in a case of metastatic ASPS, Xu et al 12 reported aberrant CD68 immunopositivity in 2 cases of ASPS, diagnosed on cytology, including the characteristic t(X;17)(p11;q25) translocation in a single case. In one of the earlier reported cases of translocation‐related RCC, tumour cells were found to be positive for CD10 and TFE3.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Alveolar soft part sarcoma is known to be associated with some uncommon clinical and morphological features, along with variable immunohistochemical staining results. [11][12][13] Apart from a few reported cases, there is no documented series on FNAC of ASPS confirmed with TFE3 immunohistochemical staining.…”
Section: Introductionmentioning
confidence: 99%